Survey on 3D biometric traits for human identification - Gangachannaiah, Divya; Shivaraj, Mamatha Aruvanalli; Nagaraj, Honganur Chandrasekharaiah; Paga, Prasanna Gururaj (IAES International Journal of Artificial Intelligence (IJ-AI), 2025)
Individuals are verified and identified using Biometric technology based on their biological or behavioral traits. Biometric-based personal authentication systems are more reliable and user friendly, overruns the traditional personal authentication systems. The physiological biometric traits get abraded due to aging and massive work, while the behavioral biometric traits are having high variations due to external factors such as fatigue, and mood. Among the physiological biometric traits, Finger geometry patterns are widely deployed authentication system reason being its stability, user acceptability and uniqueness. Recent trends in Biometrics attempt to incorporate 3D domain traits, 3D reconstruction is done using 2D multiple images. 3D images are usually more robust and illumination invariant as compared to their 2D counterparts. 3D reconstruction algorithms are compared by finding mean square error (MSE).